THE IMPACT OF BROKEN HOMES ON FAMILY BUSINESSES - Sumartlie, Duncan Shawn; Hermeindito, (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This study aims to explore the impact of broken homes on family businesses using a qualitative narrative approach. Informants who met the criteria were three (3) members of management from family businesses that had experienced the impact of broken homes, one psychologist, and one business expert. In this study, theory triangulation was used to test the validity of the data. This study is expected to provide in-depth insights into how fractured family dynamics can affect the sustainability and management of family businesses. By understanding the various challenges and adaptation strategies faced by business actors, this study seeks to provide recommendations that can support the resilience and growth of family businesses amid less-than-ideal family situations. The results of this study can be a valuable source of information for academics, business practitioners, and individuals who come from broken homes and are involved in family businesses.